Identifying predictive factors for long-term visual recovery after corneal endothelial keratoplasty in Fuchs' dystrophy: Potential interaction between the corneal dysfunction and retinal status - Maffre, Charlotte; Fournié, Pierre; Durbant, Eve; Arndt, Carl; Djerada, Zoubir; Denoyer, Alexandre (Frontiers in Medicine, 2023)
Descemet membrane endothelial keratoplasty (DMEK) is the main treatment for Fuchs’ dystrophy (FECD). The outcomes are excellent, but the final visual recovery may vary from patient to patient with sometimes no obvious reason of such a spread. We conducted a clinical prospective multicentric study to identify the predictive factors for the visual result one year after surgery. 83 patients (83 eyes) were included. Postoperative BCVA after one year was 0.20 ± 0.18 logMAR. Logistic regression revealed that good visual recovery correlated negatively with preoperative central macular thickness (p < 0.001) and the need for rebubbling (p = 0.05), and positively with preoperative visual acuity (p = 0.009). Multivariate formula to predict the one-year BCVA has been suggested. Preoperative retinal status seems to be the main predictive factor for long-term visual result after DMEK, suggesting that a pre-existing corneal–macular interaction may influence the outcomes. Our predictive multivariate model could assist in better informing the patient about the prognosis of the surgery, and in adjusting the therapeutic strategy also, further highlighting the essential collaboration between both cornea and retina subspecialists.